2010
DOI: 10.3109/03009730903431809
|View full text |Cite
|
Sign up to set email alerts
|

First-time parents' experiences of home-based postnatal care in Sweden

Abstract: AimTo gain a deeper understanding of first-time parents' experiences of early discharge from hospital after delivery and home-based postnatal care.Material and methodsThe study was comprised of focus group interviews, interviews with couples and with fathers. Twenty-one parents participated. Inclusion criteria: healthy women who have given birth to their first child after a normal pregnancy and delivery, the women's partners, healthy and full term babies, Swedish-speaking, discharge from the delivery ward with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 27 publications
(28 reference statements)
4
94
1
4
Order By: Relevance
“…They did not feel that they were disturbing the staff when sending a written message, in comparison with making a synchronous phone call. This has been described in the literature as an issue because new parents are reluctant to contact health-care professionals in case they disturb them, even when they have important questions (Johansson et al, 2010;Danbjørg et al, 2013). Other studies within different specialties have also shown that asynchronous communication can be a way to overcome this barrier.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They did not feel that they were disturbing the staff when sending a written message, in comparison with making a synchronous phone call. This has been described in the literature as an issue because new parents are reluctant to contact health-care professionals in case they disturb them, even when they have important questions (Johansson et al, 2010;Danbjørg et al, 2013). Other studies within different specialties have also shown that asynchronous communication can be a way to overcome this barrier.…”
Section: Discussionmentioning
confidence: 96%
“…Qualitiative studies have shown that new mothers, and their partners, who are discharged early from hospital experience a lack of support, have many doubts and feel insecure (McLachlan et al, 2009;Johansson et al, 2010;Persson et al, 2011;Danbjørg et al, 2013). A sense of security is important as it may influence an individual's journey towards becoming an effective parent.…”
Section: Introductionmentioning
confidence: 95%
“…There is a need for greater flexibility in providing early postnatal discharge (McLachlan et al, 2008). Midwifery care in the home environment is rated highly by those women who have access to home-visiting midwifery services (Fereday et al, 2009;Fenwick et al, 2010;Johansson et al, 2010). First-time mothers have expectations about continued contact with the maternity ward staff, i.e.…”
Section: Feeling Self-confidentmentioning
confidence: 98%
“…5 The transition to parenthood is one of the greatest challenges facing families and the people who compose them. This transition to and experience of parenthood have been the target of several studies, [6][7][8][9][10] which created room for the establishment of interventions by healthcare professionals to promote family health at times such as this that are particularly critical and intense.…”
Section: Introductionmentioning
confidence: 99%